THE METHODOLOGICAL CONFLICT BETWEEN THEORY AND PHILOSOPHY OF LAW: : THE CONSERVATIVE LEGAL ANALYSIS - S. Shestopal, Sergey; A. Kazachanskaya, Elena; V. Kachurova, Svetlana; V. Kachurov, Evgeniy (Revista Gênero e Interdisciplinaridade, 2021)
The subject of this research is the recently intensified competition in modern jurisprudence of two equally respectable scientific disciplines: philosophy of law and theory of law. The goal is to demarcate the meaning of these concepts. Their ontological status (essential significance) in relation to the existence of the law, the reflection of which they are, is also considered. Based on analysis of the existential criticism of the dominant forms of modern ideology, it is proved that the existing theories of law depend on these forms. A stable tendency in modern philosophy to return legal science to the origins of philosophical knowledge of legal reality is stated.